Wound Care (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Wounds and the many associated problems have challenged health care providers for centuries and today, despite the wealth of knowledge available, neither the incidence nor prevalence of wounds is reducing. Furthermore, in view of our changing demographic profile and the projected increase in the older population it is likely that wound management will become an ever increasing burden to the individual, health care services and society as a whole. The annual incidence of wounds in the EU-27 is approximately 4 million, and between 25% and 50% of acute hospital beds are occupied by patients with a wound, with up to 60% of these representing non-healing wounds (infected surgical wounds, pressure ulcers, leg/foot ulcers) The increasing prevalence and incidence of non-wounds healing is closely linked with quality of care and, as such, these rising figures reduce society’s confidence in the health service’s ability to deliver care that is timely, appropriate and effective. Thus, for those involved in this specialist area of clinical practice, the fundamental goal is to improve clinical outcomes, reduce the burden of wounds and improve health related quality of life. In this Special Issue “Wound Care” in Healthcare, we invited submission of manuscripts exploring contemporary issues in wound care. By devoting a special issue to wound care, we endeavoured to provide readers with a comprehensive reference source, outlining key areas of interest in this important aspect of clinical practice. The response to the call for manuscripts was fantastic and, as a result, we were able to include both original qualitative and quantitative research papers in addition to review papers, thereby providing readers with a wealth of valuable information pertinent to wound care.